From Synthesis to Application: Advances in Macrocyclic Complexes - Abbas, Nabaa; Alabdali, Ammar Jihad; Al-Mashhadani, Mohammed Hussein; Alhuwaymil, Zamzam; Alyami, Mohammed Saeed; Alshareef, Sohad Abdulkhaleq (Universitas Gadjah Mada, 2025)
Macrocyclic complexes, characterized by their large ring structure incorporating multiple donor atoms, have garnered significant attention due to their pivotal roles in both natural and synthetic systems. This review examines the synthetic methods of macrocyclic ligands and their metal complexes, highlighting their structural intricacies and coordination behaviors. The multifaceted applications of these complexes span various domains in pharmaceuticals as they enhance drug solubility and bioavailability; in catalysis, they facilitate oxidation reaction and water splitting processes; in sensing, calixarenes serve as selective ion and molecule detectors; and in biomedicine, certain macrocyclic compounds exhibit potential in targeting cancer stem cells. Despite these advancements, challenges persist, notably in achieving efficient macrocyclization and ensuring stability under diver’s conditions. Future directions emphasize the incorporation of stimuli-responsive supramolecular assemblies to enhance drug delivery mechanisms and therapeutic interventions. This comprehensive overview emphasizes the importance of macrocyclic complexes in advancing chemical science and their potential in addressing contemporary scientific challenges.